2011
DOI: 10.1002/hep.24074
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-28B polymorphisms are associated with histological recurrence and treatment response following liver transplantation in patients with hepatitis C virus infection

Abstract: Background Polymorphism in the IL28B gene region, encoding interferon-lambda(λ)-3, is strongly predictive of response to antiviral treatment in the non-transplant setting. We sought to determine the prevalence and impact on clinical outcomes of donor and recipient IL28B genotypes among liver transplant recipients. Methods Cohort study including 189 consecutive hepatitis C virus (HCV) patients who underwent liver transplantation between 1-1-1995 and 1-1-2005 in the Mayo Clinic, Rochester. Genotyping of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
191
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(214 citation statements)
references
References 19 publications
19
191
2
2
Order By: Relevance
“…Genetic variants of IL28B explain differences in IFN efficacy between races due to different distributions of individual gene alleles [7][8][9][10][11]. Studies on HCV provided an inspiration for investigations of the influence of IL28B polymorphisms on infections with the other hepatotropic viruses, since IFN λ shows broad and non-specific antiviral activity [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants of IL28B explain differences in IFN efficacy between races due to different distributions of individual gene alleles [7][8][9][10][11]. Studies on HCV provided an inspiration for investigations of the influence of IL28B polymorphisms on infections with the other hepatotropic viruses, since IFN λ shows broad and non-specific antiviral activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous genotypes classified as CC at locus rs12979860 were associated with more than twice as high SVR rate in comparison with TT alleles, whereas CT heterozygotes exerted an intermediate treatment response [7][8][9][10]. A favorable CC constellation was also shown to increase spontaneous HCV clearance and predicts better outcomes of HCV reinfection after liver transplantation [11].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the impact of genetic differences in donor and recipient may vary according to the duration of post-transplant follow-up [57]. Results of intensive investigations demonstrated that donor polymorphisms of IL-28B-gene may partially predict the outcome of antiviral treatment [60].…”
Section: Genetic Variants In Donormentioning
confidence: 99%
“…A SNP in this locus (rs12979860) has been shown to be associated with the development of at least F2 fibrosis in the graft 1 year after transplantation in 154 HCV-infected recipients [12]. Again, as for the TLR4 SNP, only the recipient genotype but not the donor genotype, was predictive of fibrosis progression.…”
mentioning
confidence: 98%
“…Three recent studies have analyzed a higher number of HCVinfected patients and have provided follow-up data for at least 5 years [11][12][13]. The first of these studies assessed the importance of a nonsynonymous TLR4 SNP (D299G) on graft survival following LT.…”
mentioning
confidence: 99%